DAMPAK SISTEM PENJAMINAN MUTU AKADEMIK TERHADAP KUALITAS PELAYANAN AKADEMIK DI STMIK DHARMA WACANA METRO - Kindiasari, Aktansi (Jurnal Manajemen Magister Darmajaya, 2017)
Globalization and free  trade  area  has  caused all organization change  their paradigm, including the higher education sector. To make sure that the process within auniversity has matched the proposed criterias, every university try to developan internal quality management system and complete it with standardized quality. Previous research were only try to find the correlation between internal quality management starndard and performance. This research is conducted in STMIK Dharma Wacana to know whether academic quality assurance system has an influence on improving the quality of academic service in STMIK Dharma Wacana. Pearson product moment correlation method is used to analyze the results of research that showed positive and significant results on the research hypothesis that was built. It shows that the implementation of the academic quality assurance system has an influence on improving the quality of academic services in STMIK Dharma Wacana. For further research can be tested external quality assurance system other to see the effect on the performance of universities.Keywords: Quality, quality management, service quality, performance